Strategi Integrated Marketing Communication pada Bisnis Fotografi: Studi Kasus Perancangan Komunikasi Pemasaran "restu Ibu" - Fatih Al Hakim Hadiwarsa; Aulia Suminar Ayu (Jurnal Komunikasi Massa, 2025)
Social media influences the development of photography services, marked by the increasing number of services in this field. However, not all photography services, especially weddings, have succeeded in utilizing social media effectively to increase sales and brand awareness. The researcher wants to know how the Integrated Marketing Communication Strategy is in the "Restu Ibu" Photography Business. The researcher provides research limitations using the Integrated Marketing Communication method. The approach method for this thesis is qualitative descriptive using purposive sampling techniques. The sources in this study were three sources from different divisions, namely the marketing, editor and photography divisions. The data validity test in this study used the source triangulation technique (member checking). The data analysis technique in this study used the interactive model, Miles and Huberman in (Pawito, 2017). Based on the results of research on the integrated marketing communication (IMC) strategy in the “Restu Ibu” photography business, it can be concluded that “Restu Ibu” uses various communication channels such as social media Instagram and TikTok which are managed with consistent visual narratives, full of emotion, and according to audience characteristics in implementing Integrated Marketing Communication.